The Effect of Digitalization, Advertising Attractiveness and Product Variety on Community Purchasing Decisions on MSME Products in Medan City - Cristofer, Alfonco Frans; Pandia, Renata Gitara; Rindorindo, Restika; Sibarani, Hendra Jonathan; Simanjuntak, Owen de Pinto (Lembaga Riset Ilmiah, 2023)
The failure of existing product variations can be caused by an undeveloped brand image among consumers, lack of consumer confidence, decreased product desirability, and deviation of the wrong product due to incorrect analysis, because many consumers do not know the existing products in meeting consumer needs. This research uses quantitative methods, with descriptive analysis techniques and is explanatory research with a sample of 100 respondents. Data analysis in this study used the SPSS. The results showed that the Sig value to influence digitalization on purchasing decisions is 0.003 < 0.05 and the tcount value is 3.044 > ttable 1.985, the Sig value to influence the attractiveness of advertising on purchasing decisions is 0.017 < 0.05 and the tcount value (2.440) > ttable (1.985), the Sig value for influencing product variations on purchasing decisions is 0.017 < 0.05 and the tcount value (2.435)> ttable (1.985), it can be stated that product digitalization, attractiveness of advertising, product variety have a positive and significant effect on purchasing decisions